ACUTE RELATIONSHIPS BETWEEN MENTAL HEALTH AND COGNITIVE FUNCTION AMONG AGING ADULTS DURING THE COVID-19 PANDEMIC. (20th December 2022) - Kobayashi, Lindsay; O'Shea, Brendan; Joseph, Carly; Finlay, Jessica
Abstract: The acute impacts of COVID-19-related mental health concerns on cognitive function among aging adults are unknown. We investigated whether between-person (BP) differences and within-person (WP) changes in loneliness, anxiety, and COVID-19 worry were related to cognitive function and abilities in the COVID-19 Coping Study over nine months from August/September 2020 through April/May 2021 (n=2, 262). Marginal structural models accounting for depression as a time-varying confounder and incorporating attrition and sampling weights estimated the BP and WP relationships of loneliness, anxiety, and COVID-19 worry with PROMIS cognitive function and abilities scores over time. In any given month, experiencing a loneliness or anxiety score higher than the sample mean (BP difference) as well higher than one's personal mean across the nine-month period (WP change) were negatively associated with cognitive function and abilities in that month. Future research should explore long-term impacts of loneliness and anxiety experienced during the pandemic for population cognitive aging.